Análise da influência de diferentes tratamentos térmicos na nitretação do aço AISI H13 - Hilgenberg, Felipe Khouri (2015)
Nitriding process is widely used in order to improve mechanical properties of steels, such as surface hardness and wear resistance. Among steels used in heavy wear applications, the AISI H13 has wide industrial usage. There is a great amount of research focused on the thermochemical parameters to be used on the nitriding process, few has been researched on the influence of heat treatments to be done before nitriding. and their influence on the properties of the part after the nitriding This work has studied the influence of various hardening and tempering temperatures on plasma nitriding. In order to do so, samples were carachterized by being submited to both core and surface hardness tests, nitrided layer thickness tests, scratch tests, and characterizing using an optical microscope. There was found no relation between heat treatments and nitrided surface hardness or thickness. There could be observed, though, influence of the heat treatments and the drag coefficient, scratch depth and scratch hardness.